2020
DOI: 10.1371/journal.pone.0231451
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific expression profiles of ecdysteroid biosynthesis and ecdysone response genes in extreme sexual dimorphism of the mealybug Planococcus kraunhiae (Kuwana)

Abstract: Insect molting hormone (ecdysteroids) and juvenile hormone regulate molting and metamorphic events in a variety of insect species. Mealybugs undergo sexually dimorphic metamorphosis: males develop into winged adults through non-feeding, pupa-like stages called prepupa and pupa, while females emerge as neotenic wingless adults. We previously demonstrated, in the Japanese mealybug Planococcus kraunhiae (Kuwana), that the juvenile hormone titer is higher in males than in females at the end of the juvenile stage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…It is important to bear in mind that the differences we describe in this study are found in adult whole‐body samples and thus do not capture expression and DNA methylation biases between tissues and developmental stages, which are known to vary greatly (Grath & Parsch, 2016; Harrison et al, 2015). Recently, both sex‐specific and developmental stage‐specific expression has been identified in other mealybug species: Phenacoccus solenopsis (Omar et al, 2019), Planococcus kraunhiae (Muramatsu et al, 2020) and Maconellicoccus hirsutus (Kohli et al, 2020). With Kohli et al (2020) identifying sex‐specific expression of numerous epigenetic regulators, including the genes SMYDA ‐ 4 and SDS3 which are up‐regulated in males and SMYD5 and nucleoplasmin which are up‐regulated in females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to bear in mind that the differences we describe in this study are found in adult whole‐body samples and thus do not capture expression and DNA methylation biases between tissues and developmental stages, which are known to vary greatly (Grath & Parsch, 2016; Harrison et al, 2015). Recently, both sex‐specific and developmental stage‐specific expression has been identified in other mealybug species: Phenacoccus solenopsis (Omar et al, 2019), Planococcus kraunhiae (Muramatsu et al, 2020) and Maconellicoccus hirsutus (Kohli et al, 2020). With Kohli et al (2020) identifying sex‐specific expression of numerous epigenetic regulators, including the genes SMYDA ‐ 4 and SDS3 which are up‐regulated in males and SMYD5 and nucleoplasmin which are up‐regulated in females.…”
Section: Discussionmentioning
confidence: 99%
“…Planococcus kraunhiae (Muramatsu et al, 2020) and Maconellicoccus hirsutus (Kohli et al, 2020). With Kohli et al (2020) identifying sexspecific expression of numerous epigenetic regulators, including the genes SMYDA-4 and SDS3 which are up-regulated in males and SMYD5 and nucleoplasmin which are up-regulated in females.…”
Section: Future Considerationsmentioning
confidence: 99%
“…Ecdysteroid signaling, including the Sad gene, is associated with sexual dimorphism in addition to molting and metamorphosis in insects. For example, ecdysteroids contribute to extreme sexual dimorphisms in mealybugs, whose mRNA expression levels from the second nymphal instar to adult stages were higher in males than in females [ 69 ]. In beetles, ecdysteroids have been reported to control horn length dimorphisms in male heads [ 70 ], and Halloween genes, including Shade ( Shd ) and Phm , have been suggested as candidate target genes that are downregulated by the Dsx gene [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…In adult male insects ecdysteroids have been shown to be crucial for male fertility and development of the reproductive system (Dalton et al, 2009;Ganter et al, 2011;Herndon et al, 1997;Ishimoto et al, 2009;Leiblich et al, 2019;Muramatsu et al, 2020;Sharma et al, 2017;Shinbo and Happ, 1989;Xu et al, 2020). In insects, spermatozoa produced by the testes are stored in paired seminal vesicles, which are surrounded by the male accessory glands (MAG).…”
Section: Introductionmentioning
confidence: 99%
“…MAG protein synthesis and sperm production were affected in the red flour beetle, Tribolium castaneum, after an RNAi-induced knockdown of several nuclear receptors that play a role in the 20E-induced signaling cascade (E75 or HR38 and E78 or HR39, respectively) (Xu et al, 2020). Muramatsu et al (2020) suggested that higher ecdysteroid titers in males of the Japanese mealybug, Planococcus kraunhiae, drive male development and cause extreme sexual dimorphism. These studies contributed to the increasing evidence supporting an important role of ecdysteroids in male reproductive physiology, and more specifically MAG development and activity.…”
Section: Introductionmentioning
confidence: 99%